Assessing the Role of Women in Tourism Related Sectors in the Caribbean - Francesco Pastore; Allan Webster; Kevin Hope (Institute of Labor Economics (IZA), 2020)
This study contributes to the rapidly growing literature on women in tourism. It focuses on a group of 13 Caribbean countries. The study analyses the impact of women in apical positions within firms (top manager or owner) on firm performance – productivity, profitability and female employment. For this both a decomposition model and the Inverse Probability Weighted Regression Adjustment (IPWRA) estimator are used. The analysis finds that opportunities for women in these positions in the Caribbean are constrained to less productive and profitable firms, as elsewhere. However, those firms with females at the top employ more women, particularly in management roles.
Keywords: D22; J16; L26; L83; Z32; 330; gender differences; tourism; propensity score matching; IPWRA; Caribbean